Location Of Superior Parathyroid Glands During Intraoperative Thyroidectomy In Patients With Multinodular Goiter: A Prospective Observational Study (Journal of Pharmaceutical Negative Results, 2023)
Thyroid disease affects roughly 20 million Americans. Although thyroidectomy is a very safe surgical technique, meticulous thyroid dissection is required to avoid harming other critical structures such as the parathyroid gland and its vasculature. Accidental removal of parathyroid glands can occur in 4-18% of thyroidectomies, resulting in hypocalcemia-related adverse effects. To determine the location of superior parathyroid glands during intraoperative thyroidectomy in patients with multinodular goiter presenting to a tertiary care hospital. One hundred and nine patients presenting with a multinodular goiter were included in this study on Inpatient basis from January 01, 2022 to December 30, 2022 in the department of Otorhinolaryngology-A unit of Hayatabad Medical Complex, Peshawar, based on observational cross sectional study design, prospective data collection and non-probability convenience sampling technique, patients aged from 30 to 60 were included in this study with disease of Multinodular goiter of thyroid. Patients having diseases and tumors of parathyroid were excluded from the study. Majority of the study sample consisted of females 71 females (65.1%) while 38 males (34.9%) were male (N=109). In 21 (19.3%) of patients the superior parathyroids were identified in the tracheoesophageal grooves on both sides of the thyroid gland. There were no superior parathyroid glands near the superior ala of thyroid cartilage. In 88 (80.7%) they were 1cm away from the intersection of RLN and inf. Thyroid artery. The results of our study concluded that 80% of superior parathyroid glands lie 1cm within the intersection of Recurrent laryngeal nerve with the inferior thyroid artery while 19.3% lie near the treacheoesophageal groove.